Beyond Fun: Teacher’s Challenges in Integrating Joyful, Mindful, Meaningful Learning In English Language Teaching - Yasminar Amaerita Telaumbanua; April Niwati Gea; Bitta Maria Waruwu; Alvin Ebenezer Zamasi; Celsia Angelin Gulo (English Language Teaching Methodology, 2025)
The Merdeka Curriculum promotes a deep learning paradigm through the integration of joyful, mindful, and meaningful learning. However, classroom practices in Teaching English to Young Learners (TEYL) frequently prioritize enjoyment while neglecting cognitive depth and reflective awareness, creating a critical gap between policy expectations and pedagogical implementation. This study aims to examine the challenges faced by English teachers in integrating joyful, mindful, and meaningful learning within English language instruction. Employing a qualitative descriptive approach, this study was conducted at SDN 078010 Banuasibohou Onozikho. The participants comprised one English teacher and sixteen fifth-grade elementary school students. Data were collected through classroom observations and semi-structured interviews and analyzed thematically. The findings reveal that joyful learning was the most consistently implemented dimension, as reflected in high student enthusiasm, active participation, and a positive classroom atmosphere. In contrast, mindful and meaningful learning were insufficiently developed. Students tended to rely on rote repetition with limited conceptual understanding or transfer of knowledge, while teachers encountered persistent difficulties in maintaining students’ focus and self-regulation. These challenges were further intensified by limited instructional resources, restricted instructional time, and uneven student readiness. This study contributes novel empirical evidence from a rural primary school context, highlighting the imbalance in the implementation of deep learning dimensions under the Merdeka Curriculum. The findings underscore the urgency of providing systematic pedagogical support, adequate learning materials, and continuous professional development to enable teachers to integrate joyful, mindful, and meaningful learning more effectively in English language teaching